China’s Indigenous Social Rural Pension: Building Ground Work for Future Research - Wang, Jingjing; Wang, Haolin; Yang, Xiangqian; Hao, Yajie; Ma, Guoxin (INTI International University, 2020)
China has the largest elderly population in the world, while its overall population has been unprecedentedly growing for quite some time now. The aging population is particularly concerning in China where the ‘family is traditionally responsible for taking care of their elders as there is no established, sustainable social security system’ especially in rural areas. Worse still, the one child policy and the rapid urbanisation processes resulting in younger adults leaving rural areas for better jobs and lifestyles since the 1990s have put greater pressures on rural families who have fewer younger people to depend on for taking care of their elderlies. Against this background, there is an urgent need to build ground work for future research which can shed more light on social organisations for the rural elderly in China, giving particular attention to indigenous features in the Chinese context – a contribution this paper offers to make.